Pengembangan Majalah Kimia Dengan Konten Kondensasi Formaldehida Sebagai Suplemen Bacaan Pada Perkuliahan Mekanisme Dan Sintesis Senyawa Organik - Rahmawati, Rahmawati; Hidayati, Elya; Al Idrus, Syarifa Wahidah (Chemistry Education Practice, 2025)
The Organic Compound Mechanism and Synthesis Lecture (MSSO) is one of the important courses in the chemistry education study program, which discusses the process of forming organic compounds through various chemical reaction. The limited learning media used, which is only in the form of textbooks, also causes the learning process to be less interesting. Therefore, an interesting and easy to understand learning media innovation is needed. This research aims to develop a reading supplement in te form of a chemical magazine with formaldehyde condensation content as supporting media for MSSO lectures, as well as to determine the level of validity and feasibility. The research methode used is research and development (R&D) with a 4D (define, design, develop, disseminate) model. The result of the validation of the chemical magazine by 3 (three) validators showed a validity coefficient value of 0,93 with a very valid category, and a reliability value of 95%. Student responses to chemistry magazines showed a very practical category with a score 84.98%..